Financial planning for retirement among private sector employees in Sri Lankan financial institutions - Bandara, Sunari; Durairatnam, Sakunthala (Technium Social Sciences Journal, 2025)
Though there exists a substantial potential market for retirement plans in Sri Lanka, the demand for retirement plans is considerably low. The current study investigates the reasons for such a gap, in light of the Capacity-Willingness-Opportunity model. Adopting a positivist stance and a deductive approach, the study attempts to determine whether financial self-efficacy, job involvement, and social group support are significant factors that should be considered as components of capacity, willingness, and opportunity to save for retirement, respectively. It also investigates whether the effects of the exogenous variables on the endogenous variable would be moderated by gender and/or age group. Using data from 376 employees collected through structured self-administered questionnaires, the study employs PLS-SEM to analyze data. The study finds that social group support and financial self-efficacy have a significant and positive impact on financial planning for retirement (FPR), whereas job involvement does not. Albeit not significantly different from men, women have greater effects of financial self-efficacy, job involvement, and social group support on FPR. When one is in a greater age category, the influence of financial self-efficacy on FPR is substantially greater.